Implementasi Sila Pertama Pancasila dalam Pembentukan Karakter Religius Anak Usia Dini: Studi Kasus TK AL-ROSY Desa Cipeundeuy Kecamatan Bojong Purwakarta - Dzikri Abazis Subekti; Said, Hadi M. Musa; Fachrudin, Alif Pasah; Holijah, Siti; Puspitasari, Devi (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study analyzes the implementation of the first principle of Pancasila, Belief in the One and Only God, in the curriculum and daily practices at AL-ROSY Kindergarten (TK), Cipeundeuy Village, Purwakarta. Instilling spiritual values ​​from an early age is essential to build the foundation of religious, tolerant, and noble character in accordance with the national identity. The research method used is descriptive qualitative through case studies, involving participatory observation and in-depth interviews with the principal, teachers, and analysis of curriculum documents. The results show that AL-ROSY Kindergarten applies an integrative strategy through three aspects: 1) Habituation of religious rituals (Duha prayer, prayer, and memorization) as a manifestation of obedience; 2) Utilization of nature-based media and the surrounding environment to introduce the concept of God's power and majesty; and 3) Emphasis on social morals (tolerance and infaq) as a concrete manifestation of faith in daily interactions. This finding confirms that AL-ROSY Kindergarten has succeeded in making the value of Belief in the One Almighty God the philosophical and practical foundation in all educational programs, resulting in an integrated and contextual model of character value instillation.